2023
DOI: 10.1002/smll.202207941
|View full text |Cite
|
Sign up to set email alerts
|

A Heterogeneous Single Atom Cobalt Catalyst for Highly Efficient Acceptorless Dehydrogenative Coupling Reactions

Abstract: A fundamental understanding of metal active sites in single‐atom catalysts (SACs) is important and challenging in the development of high‐performance catalyst systems. Here, a highly efficient and straightforward molten‐salt‐assisted approach is reported to create atomically dispersed cobalt atoms supported over vanadium pentoxide layered material, with each cobalt atom coordinated with four neighboring oxygen atoms. The liquid environment and the strong polarizing force of the molten salt at high temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…[30][31][32][33] Therefore, a comprehensive understanding of the electronic metal-support interaction (EMSI) mechanism and the rational design of SACs via elaborately modulated EMSI for high-performance catalytic reactions are urgently needed. [34][35][36][37][38] Hexagonal boron nitride (h-BN) is a graphene-like material with excellent stability and a large specic surface area, which makes it an excellent support in heterogeneous catalysis. [39][40][41][42][43][44] In addition, the surface functionalization of h-BN can advantageously improve the interaction with metal atoms, and previous studies have shown that BN plays an important role in hydrogenation reactions, and defect-rich BN is used as a catalyst carrier for selective hydrogenation of organic compounds such as dimethyl oxalate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32][33] Therefore, a comprehensive understanding of the electronic metal-support interaction (EMSI) mechanism and the rational design of SACs via elaborately modulated EMSI for high-performance catalytic reactions are urgently needed. [34][35][36][37][38] Hexagonal boron nitride (h-BN) is a graphene-like material with excellent stability and a large specic surface area, which makes it an excellent support in heterogeneous catalysis. [39][40][41][42][43][44] In addition, the surface functionalization of h-BN can advantageously improve the interaction with metal atoms, and previous studies have shown that BN plays an important role in hydrogenation reactions, and defect-rich BN is used as a catalyst carrier for selective hydrogenation of organic compounds such as dimethyl oxalate.…”
Section: Introductionmentioning
confidence: 99%
“…30–33 Therefore, a comprehensive understanding of the electronic metal–support interaction (EMSI) mechanism and the rational design of SACs via elaborately modulated EMSI for high-performance catalytic reactions are urgently needed. 34–38…”
Section: Introductionmentioning
confidence: 99%
“…In our initial catalyst reaction mechanistic considerations, the phosphorus atom is replaced by oxygen in the lattice during the construction of Co−P−O1, Co−P−O2, and Co−P−O3 (Figure S8). The DFT results (Figure 5a 47 In general, the polarization and rearrangement of overall surface charge and delocalization effects of d electrons would be enhanced with the introduction of O, while excessive oxygen content would be unfavorable to the adsorption of the reactant. 48 Thus, the appropriate oxygen content in Co−P−O2 could optimize the adsorption of H 2 O/OH − and the desorption of H 2 /O 2 for enhancing HER and OER activities in alkaline conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Electron localization function (ELF) results of Co–P–O1, Co–P–O2, and Co–P–O3 are shown in Figure g–i. The ELF results indicate that the electronic structure of the Co–P bond is more active and delocalized when oxygen atoms are incorporated into pure CoP . In general, the polarization and rearrangement of overall surface charge and delocalization effects of d electrons would be enhanced with the introduction of O, while excessive oxygen content would be unfavorable to the adsorption of the reactant .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, various homogeneous and heterogeneous noble and non-noble metal catalysts have been explored for the direct coupling of alcohols and amines to imine. Ruthenium-based catalysts are among the most active and effective metal-based catalysts in this field, catalyzing this dehydrogenative condensation reaction either with an oxidant (typically, O 2 or air) or even in the absence of any oxidants under an inert atmosphere. While the latter could largely avoid overoxidation of alcohols to carboxylic acids, it might also be faced with a significant decrease in reaction selectivity caused by the formation of amine byproducts as a result of the reaction of imine products with the hydride species generated during the dehydrogenation process. , Moreover, some of the catalytic systems presented for the coupling of alcohols with amines under inert conditions have drawbacks such as using large amounts of poorly accessible, expensive, complex, and yet nonrecyclable homogeneous catalysts, using additives, requiring high reaction temperatures, and needing to conduct the reactions under an Ar/N 2 atmosphere. Therefore, it seems that the aerobic oxidative coupling of alcohols and amines, especially by employing heterogeneous and recoverable catalytic systems, is still an active and preferable approach to the synthesis of imines.…”
Section: Introductionmentioning
confidence: 99%